2019
DOI: 10.1186/s12913-019-4650-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a mandatory DRG payment system in South Korea: Analysis of multi-year nationwide hospital claims data

Abstract: BackgroundIn 2002, a voluntary diagnosis-related groups (DRGs) payment system was introduced in South Korea for seven disease groups, and participation in the DRGs was mandated for all hospitals beginning in 2013. The primary aim of this study was to compare results reflective of patient care between voluntary participation hospitals (VPHs) and mandatory participation hospitals (MPHs) governed by either the DRGs or fee-for-service (FFS) payment system.MethodsWe collected DRGs and FFS inpatient records (n=3,038… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…The nding application of ERAS can reduce the costs and LOS may assist staff and patients pay more attention to the application of ERAS during clinical practice. DRGs payment system was introduced and mandated worldwide for its potential to curbing unnecessary resource and cost-saving implications by decreasing costs and LOS [28,29]. Relevant literatures re ected that healthcare system assess satisfaction and quality of the inpatients, which highlights the speci cation of ERAS [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The nding application of ERAS can reduce the costs and LOS may assist staff and patients pay more attention to the application of ERAS during clinical practice. DRGs payment system was introduced and mandated worldwide for its potential to curbing unnecessary resource and cost-saving implications by decreasing costs and LOS [28,29]. Relevant literatures re ected that healthcare system assess satisfaction and quality of the inpatients, which highlights the speci cation of ERAS [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all inpatients, about half of patients in the emergency department, and nearly one-third of outpatients had laboratory results during their visit to the health-care center, 15 comprising a quite portion (5-6%) of the total cost of healthcare. 16,17 If we can improve the quality of CBC's lab test reports, coupled with future cloud consolidation to avoid duplicate testing…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all inpatients, about half of patients in the emergency department, and nearly one-third of outpatients had laboratory results during their visit to the health-care center, 15 comprising a quite portion (5–6%) of the total cost of healthcare. 16 , 17 If we can improve the quality of CBC’s lab test reports, coupled with future cloud consolidation to avoid duplicate testing in the different hospitals even the same hospital, we believe that many health insurance medical expenses can be reduced, while improving the quality of care. At present, there is no golden standard protocol for clinical test personnel to perform parallel testing of QC reagents with new and old batch numbers as part of their CBC routine.…”
Section: Discussionmentioning
confidence: 99%
“…DRGs bear inherent risks of potential harm to patients by quality of health services to reduce the cost of healthcare. Previous studies showed that implementing DRGs decreased the duration of stay and out-of-pocket costs [ 5 ] as well as significantly reducing examination fees relative to fee-for-service (FFS) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory tests are a large part of modern medicine. Nearly all inpatients, about half of patients in the emergency department, and nearly one-third of outpatients had laboratory results during their visit to the healthcare center [ 12 ], comprising a small portion (5–6%) of the total cost of healthcare [ 5 , 6 ]. Since poor laboratory results can significantly impact patients’ care, monitoring and improving the quality of laboratory tests is crucial [ 13 ].…”
Section: Introductionmentioning
confidence: 99%